Optimization of blood transfusion services: Analysis of blood requisition and utilization practices in cardiac surgical patients in a tertiary care hospital, India - Sadhana Mangwana; Neha Bedi; Pinky Yadav; Rakesh Chugh (Global Journal of Transfusion Medicine, 2017)
Objective: Blood products are vital resources to health-care institutions with constantly growing demands. Gross over-ordering of blood causes exhaustion of valuable supplies and resources and add financial burden to patients undergoing surgical procedure. Aims: Study was undertaken to evaluate blood requisition, utilization, and management in cardiac surgery patients in a tertiary care hospital. Materials and Methods: Prospective study was conducted in cardiac surgery patients over 3 years from 2013 to 2015. Blood utilization indices were computed. Cross match to transfusion ratio (C:T) ratio of 2.0 and below, transfusion index (TI) value of 0.5 or more, and transfusion probability (%T) value of 30% and above were considered indicative of significant blood usage. Statistical analysis was done using Student's t-test. Results: During the study, a total of 15,392 patients' requisitions were received. Out of 25,190 units of blood cross-matched, 18,741 units were issued (C:T ratio 1.34) implying that overall 25.60% of blood was unutilized. From a total of 2752 units cross-matched for cardiac surgery cases, only 1296 units were transfused with C:T Ratio 2.12 implying that 52.91% of blood was unutilized which was much higher and statistically highly significant than in total patients. Overall TI was 1.22 and %T as 83.07% while for cardiac patients, TI was 2.32 with %T as 85.84%. Conclusions: Blood transfusion plays a major role in resuscitation and management of cardiac surgery patients. Blood transfusion services need to adopt blood conserving policies. Efforts should be made to adopt more conservative transfusion thresholds, conduct regular auditing, and periodic feedback to improve blood ordering, handling, distribution, and utilization practices of this scarce resource.